Oceanographic Data of the 29th Japanese Antarctic Research Expedition from November 1987 to March 1988 - イトウ, キヨヒサ; イシイ, ミサオ; ITO, Kiyohisa; ISHII, Misao (National Institute of Polar Research, 1989)
P(論文) The cruising course of icebreaker Shirase has been changed since the summer party of the 29th Japanese Antarctic Research Expedition (JARE-29), for further study on oceanographical phenomena in the Antarctic Ocean. The stations for oceanographic observations were arranged on two lines, one is 64°S (between 50°E and 159°E) and the other is 159°E (between 64°S and Sydney). The results of the oceanographic observations on board icebreaker Shirase and tidal observation at Syowa Station are presented in this report. The oceanographic observations were carried out by the summer party of JARE-29 in 1987-1988. Tidal observation was continued through the winter mission of JARE-28 in 1986-1987. departmental bulletin paper